A differential catalogue of right ascensions of the Nikolaev zone AG stars - Bazyey, N. V.; Bazyey, A. A. (Одеські астрономічні публікації, 2017)
This catalog contains right ascentions of 4982 stars of the Nikolaev Equatorial Zone (AG, -20, +10 ) from observations made the years 1931-1935 by B.V.Novopashenny by means of the Odessa meridian circle. The observations were reduced in the FK5 system.